A method to obtain reproducible Ki‐67 indices in lung adenocarcinoma. Issue 3 (26th October 2020) - Okudela, Koji; Woo, Tetsukan; Saigusa, Yusuke; Arai, Hiromasa; Matsumura, Mai; Mitsui, Hideaki; Sugiyama, Misaki; Sekiya, Motoki; Ishikawa, Yoshihiro; Oshiro, Hisashi; Kameda, Yoichi; Ohashi, Kenichi
Abstract : Aims: Proliferative activity, evaluated from the Ki‐67 index, is a strong prognostic factor in lung adenocarcinoma (LADC). Here, we optimised a procedure to measure the Ki‐67 index and establish the best cut‐off value. Methods and results: We examined 342 stage I LADCs for the immunohistochemical expression of Ki‐67 using different antibodies, MIB1 and SP6. The results revealed the superior specificity of SP6; therefore, SP6 was used in subsequent analyses. Slides were scanned with a virtual slide system. Using software, tumour cells were counted in a whole tumour. Thereafter, the tumour was evenly subdivided into 0.25‐mm 2 tiles. The frequency of positive cells was counted in each tile of an invasive area or the whole tumour. We calculated the number of tumour cells required to produce a 95% confidence interval (CI) <0.05. Additionally, we calculated coverage probabilities (CP) using two different methods, counting any number or 200 cells per tile. The results showed that we could meet our goal by counting 2000 cells from 10 random tiles (200 cells each) in invasive areas. Conclusions: We successfully developed an optimal procedure for determination of the Ki‐67 labelling index using an SP6 antibody, which provided CP > 70% and CI of <0.05 in more than 90% of cases. Furthermore, we identified an optimal cut‐off value of 0.12 with an alternative of 0.15, based on disease recurrence. This procedure and the cut‐off values may be used in the routine pathological diagnosis of LADC.